Adaptability, yield and in vitro evaluation of some promising silage maize hybrids under tropical climate - HUNDAL, JASPAL SINGH; SINGH, GURBARINDER; WADHWA, MANJU; SHARMA, AMIT (The Indian Journal of Animal Sciences, 2019)
The study was conducted to assess adaptability, yield and in vitro evaluation of some promising silage maize hybrids (LG 32.01, LG 34.04 and BL 4121) grown under tropical climate. The experiment was conducted in completely randomized block design with 3 replications. The stand count, plant height, number of cobs and cob length remained comparable among different maize hybrids; however, LG 34.04 variety took lesser number of days for tasselling and silking as compared to BL 4121 and LG 32.01. The BL 4121 hybrid had higher biological as well as dry matter yield as compared to LG 32.01 and LG 34.04 maize varieties. Significantly higher total digestible nutrients (TDN), relative feed quality (RFQ), digestible DM and net energy for lactation (NEl) were detected in BL 4121 variety in comparison to other hybrids. Analogous total volatile fatty acids (tVFA), acetic acid (AA), propionic acid (PA), acetate to propionate ratio, ME value, digestibility of DM and OM were observed in in vitro evaluation with exception of net gas production (NGP) which was lowest for LG34.04 maize hybrid. After ensiling for 45 days, pH and lactic acid were found comparable among all selected silage maize hybrids; however, the tVFA content was recorded lowest in BL 4121 variety silage in comparison to the other hybrid silages. Furthermore, considerably higher TDN, digestible DM, NEl, RFV and RFQ in silages prepared from LG 32.01 and LG 34.04 were reported as compared to BL 4121 silage. Therefore, BL 4121 maize hybrid was superior to other varieties in herbage yield and in vitro evaluation; however maize variety LG 34.04 had better nutritive value as silage for ruminants over BL 4121 and LG 32.01 under tropical climate.